IMPROVING COMMUNICATIVE COMPETENCE OF STUDENTS BY MEANS OF MODERN INNOVATIONS AND TRENDS (American Journal of Pedagogical and Educational Research, 2023)
This article investigates the enhancement of students' communicative competence through the incorporation of modern innovations and trends in education. Focusing on diverse methodologies such as technology integration, gamification, and virtual reality, the study aims to provide insights into the effectiveness and challenges associated with these innovative approaches. The research addresses the evolving landscape of language education, emphasizing the importance of preparing students for effective communication in the contemporary world.